The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.3904/kjim.2005.20.2.129
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Aspects of Pregnancy and Delivery in Patients with Chronic Idiopathic Thrombocytopenic Purpura (ITP)

Abstract: BackgroundIdiopathic thrombocytopenic purpura (ITP) is a condition that often develops in young women and, consequently, physicians should frequently manage and monitor pregnant patients with this disorder.MethodsWe reviewed the charts of 30 women with chronic ITP delivered in 31 pregnancies from January 1995 to December 2003.ResultsFifteen patients were diagnosed with ITP before pregnancy and sixteen patients were diagnosed during pregnancy. The mean platelet counts before pregnancy, during pregnancy, and at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 15 publications
1
32
0
2
Order By: Relevance
“…137 Women with previously diagnosed ITP may experience exacerbation or relapse. 138,139 A study of 119 pregnancies in 92 women with ITP found that 31% required intervention. Pregnancy is associated with a procoagulant state in preparation for the hemostatic challenge of delivery 140 due to increased levels of fibrinogen, factor VIII, and von Willebrand factor; suppressed fibrinolysis; and a reduction in the activity of protein S. 140 These changes may result in fewer bleeding symptoms and therefore a greater tolerance to ITP in pregnant compared with non-pregnant women (evidence level IV).…”
Section: Thrombocytopenia In Pregnancy Presentation Of Thrombocytopenmentioning
confidence: 99%
See 1 more Smart Citation
“…137 Women with previously diagnosed ITP may experience exacerbation or relapse. 138,139 A study of 119 pregnancies in 92 women with ITP found that 31% required intervention. Pregnancy is associated with a procoagulant state in preparation for the hemostatic challenge of delivery 140 due to increased levels of fibrinogen, factor VIII, and von Willebrand factor; suppressed fibrinolysis; and a reduction in the activity of protein S. 140 These changes may result in fewer bleeding symptoms and therefore a greater tolerance to ITP in pregnant compared with non-pregnant women (evidence level IV).…”
Section: Thrombocytopenia In Pregnancy Presentation Of Thrombocytopenmentioning
confidence: 99%
“…Studies have shown that pregnancy in women with ITP can proceed safely with low hemorrhagic risk for both infants and mothers. 138,141,142 Because platelet counts may fall in the third trimester, the frequency of platelet count measurement increases to assist in making decisions regarding delivery. The aim of peripartum treatment is to ensure that there is a satisfactory maternal platelet count for delivery.…”
Section: Management Of Itp In Pregnancymentioning
confidence: 99%
“…The former may experience exacerbation or relapse during their pregnancy. 24,25 The managements of these Adverse events recorded in all 31 patients who take at least 1 dose of rhTPO and in their infants.…”
Section: Discussionmentioning
confidence: 99%
“…Similar distribution of patient was seen in study by Bhatet al (65%) and Won et al (51.6%), whereas in the study by Brohi et al 40.8% women were primigravida, which was slightly lower than our study. 14,23,24 In our study 63.2% women had mild thrombocytopenia. However, mild thrombocytopenia was noted in 54% and 74.7% patients included in the study by Borna et al which is lower than our study and Singh et al respectively.…”
mentioning
confidence: 90%